2011
DOI: 10.1007/s11262-011-0703-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the partial VP2 gene region of canine parvoviruses in domestic cats from Turkey

Abstract: Canine parvoviruses (CPVs) is a category comprising three closely related viruses, CPV, feline panleukopenia virus (FPLV), and mink enteritis virus, all of which cause serious diseases, especially in young cats. In this study, molecular detection and genetic analysis of a partial VP2 gene region of CPVs from domestic cats living in Turkey between 2006 and 2010 was performed by PCR amplification and sequence analysis. The results indicated that CPV-2a, CPV-2c, and FPLV were circulating in vaccinated and unvacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 37 publications
0
31
1
Order By: Relevance
“…After trimming and editing processes of the low-quality nucleotides in relevant sequences, nucleotide similarity searches by the Basic Local Alignment Search Tool (BLAST) revealed that the sequences of the blood and rectal swab samples were 98.42-99.47% identical to various CPV and FPV strains. Phylogeographic analysis of the 325 bp nucleotide sequence of the field virus with several canine and feline parvovirus sequences revealed that the obtained sequences were located inside the canine parvovirus strains with an FPV strain (HM042740.1) isolated from a cat and reported by Muz et al (22) (Fig. 1).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…After trimming and editing processes of the low-quality nucleotides in relevant sequences, nucleotide similarity searches by the Basic Local Alignment Search Tool (BLAST) revealed that the sequences of the blood and rectal swab samples were 98.42-99.47% identical to various CPV and FPV strains. Phylogeographic analysis of the 325 bp nucleotide sequence of the field virus with several canine and feline parvovirus sequences revealed that the obtained sequences were located inside the canine parvovirus strains with an FPV strain (HM042740.1) isolated from a cat and reported by Muz et al (22) (Fig. 1).…”
Section: Resultsmentioning
confidence: 64%
“…After mutations, the CPV-2 variants that have a high rate of evolution compared to FPV have become able to infect both dogs and cats and have been found in wolves, foxes, other canids and felids (14,15,32). CVP-2 has been previously reported in cats and dogs in Turkey, so obtaining up to date information representing the circulation of CPV variants is a necessity (22,28,35,39). The objective of this study was to determine the CPV variants in pups with clinical symptoms and to demonstrate its relationship with the other types reported in Turkey and around the world.…”
Section: Praca Oryginalnamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the possibility of the presence of CPV-2 strains cannot be ruled out, considering the report of isolating CPV-2 strains from cats in the neighboring country "Turkey" (Muz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The original CPV-2 was rapidly replaced with a new antigenic type CPV-2a, CPV-2b in 1979-1984(Parrish et al, 1991 and finally, the newest strain of CPV-2c was detected in 2000 in Italy (Buonavoglia et al, 2001). In contrast with the original CPV-2; CPV-2a/2b/2c earned the ability to replicate in a cat host and could also induce the clinical disease (Mochizuki et al, 1993;Truyen et al, 1996;Ikeda et al, 2000;Battilani et al, 2006a;Muz et al, 2012;Decaro et al, 2008;2011). CPV-2 variants (2a, 2b, 2c) are able to bind with feline Transferrin receptors and enter into the cells (Ikeda et al, 2002;Hueffer and Parrish, 2003) Despite CPV, FPV is evolutionarily static and develops by random genetic drift (Decaro et al, 2008) whereas the mutation rate of CPV is much higher.…”
Section: Introductionmentioning
confidence: 99%